PENGARUH KEPEMIMPINAN, BUDAYA ORGANISASI, DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADAJOLLY ROGER EDUCATION CABANG GIANYAR - Kadek Dwinata Hendrayana; Gregorius Paulus Tahu; I Gusti Ngurah Bagus Gunadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2023)
Leadership, organizational culture and communication are things that greatly affect the performance of an employee. There are concerns and findings regarding leadership problems, organizational culture and communication in an effort to improve and improve employee performance in accordance with the objectives of this study to analyze the influence of Leadership, organizational culture and communication on employee performance at Jolly Roger Education Gianyar Branch . The sampling technique in this study used a saturated sampling technique with a total sample of 60 people from the Jolly Roger Education Gianyar Branch. Data analysis in this study used Instrument Test, Classical Assumption Test, Multiple Linear Regression Analysis, Coefficient of Determination (R2), F Test and t Test. Data processing is assisted by using the SPSS Version 23 for Windows application. The results showed that leadership, organizational culture positively and communication has a positive effect on employee performance at the Jolly Roger Education Gianyar Branch.